1999
DOI: 10.2337/diabetes.48.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 192 Gln/Arg gene polymorphism, coronary artery disease, and myocardial infarction in type 2 diabetes.

Abstract: Paraoxonase is an HDL-associated enzyme implicated in the pathogenesis of atherosclerosis by protecting lipoproteins against peroxidation. Its biallelic gene polymorphism at codon 192 (glutamine/arginine) has been associated with coronary artery disease (CAD). To further evaluate the role of this paraoxonase gene polymorphism for CAD in type 2 diabetes, we determined the paraoxonase genotype in 288 type 2 diabetic patients (170 with and 118 without angiographically documented CAD). The paraoxonase 192 Gln/Arg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
57
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 35 publications
(44 reference statements)
10
57
0
Order By: Relevance
“…An adjustment for lipid and nonlipid risk factors strengthened the association between PON1 192Arg and the risk of MI. The association that we found between PON1 192Arg and MI is consistent with the results of several studies 16,20,22,24,32,33,35,36 but not all. [17][18][19]23,25 These discrepancies could be due in part to the selection criteria of the control group, to differences in case definition, and to a lack of a population-based control group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…An adjustment for lipid and nonlipid risk factors strengthened the association between PON1 192Arg and the risk of MI. The association that we found between PON1 192Arg and MI is consistent with the results of several studies 16,20,22,24,32,33,35,36 but not all. [17][18][19]23,25 These discrepancies could be due in part to the selection criteria of the control group, to differences in case definition, and to a lack of a population-based control group.…”
Section: Discussionsupporting
confidence: 93%
“…29,30 Perhaps this reduction in LDL protection (or in some other yet-to-be-identified activity conferred by PON1) explains the atherogenic effect of PON1 192Arg observed in the present and other studies. 16,20,22,24,32,33 HDL may play a significant role in the effect of PON1 on coronary disease. HDL cholesterol levels and paraoxonase protein levels are significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest in this respect is a recent study that suggests that the link we previously demonstrated between the PON B allele and the risk of vascular disease 7 may be exacerbated by smoking. 13 More important, perhaps, we demonstrate that differences in PON concentrations, on the order of those observed in the present study, can influence the ability of HDL to protect LDL from oxidation. Thus, incremental increases in HDL PON are associated with incremental decreases in the level of LDL hydroperoxides generated under oxidization conditions.…”
Section: Discussionsupporting
confidence: 58%
“…We found a 40 % decrease in PON activity in a group of Type II diabetic subjects with CAD compared with a group of non-diabetic subjects with CAD. Decreased PON in patients with Type II diabetes and CAD have also been found [44,45]. Polymorphisms within the PON gene that are prevalent in Type II diabetic patients with CAD have been reported [7,46].…”
Section: Discussionmentioning
confidence: 94%